THE EXPOSITION OF KUNDALINI YOGA IN THE YOG OPANISHADS - Mrs. Vaijayanti Navare and Dr. M. K. Sridhar (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This paper explains the exposition of Kundalini in various Yoga Upanishadas. Kundalini can be defined as the sleeping potential force or energy in the human being. It is located at the of the spinal cord. The word kundalini is derived from the Sanskrit word kundela, which means ring, circle, or coil. The dormant energy is sleeping at the base of the spine in the form of a coil having three and a half circles. So, because of this coiled form, she is named kundalini (that which is coiled). The ancient sages found that this sleeping energy can be awakened with some methods like breathing practices, mantras, yantras, meditation, postures (Asanas) and mudras, etc. They realized that by awakening this divine cosmic energy, one can reach to the ultimate reality while still in this body. (Jivanmukta state). The methods or techniques for awakening the kundalini are called as Kundalini yoga or Kundalini tantra. Kundalini yoga is considered a method of tantra tradition, but during the later period, there was a fusion of Upanishadic and Tantric traditions and the kundalini tantra got absorbed in Upanishads also